ENHANCE SERVICE APPLICATION OF STANDARD CLAUSE IN ACCOUNT OPENING AGREEMENT AT A COMMERCIAL BANK - Cesylia Anggita Fitri; Sunarmi Sunarmi; Dedi Harianto; Mulhadi Mulhadi (Sean Institute, 2023)
The agreement to open an account at a bank generally takes the form of a form provided unilaterally by the bank. The use of standard clauses in account opening agreements aims to provide practicality and convenience for the parties. However, banks must pay attention to customer rights so that no party is harmed considering the vulnerable position of customers. The aim of this research is to determine the application of standard clauses in bank account opening agreements, the legal consequences of the application of standard clauses in bank account opening agreements, as well as the form of legal protection provided to customers regarding the application of standard clauses in account opening agreements at several commercial banks in the city. Medan. The research method used is normative juridical. Data collection was carried out using literature studies and field research, data analysis was carried out qualitatively, and used a deductive conclusion drawing method. Based on the results of research conducted, there are several commercial banks in the city of Medan that include standard clauses in account opening agreements that have the potential to harm customers and are not in accordance with Law Number 8 of 1999 and POJK Number 6/POJK.07/2022. The legal consequences of applying these standard clauses are null and void and must be adjusted to statutory regulations.